2023
DOI: 10.12688/f1000research.128323.1
|View full text |Cite
|
Sign up to set email alerts
|

The experience of using Alpha-Stim AID cranial electrotherapy stimulation (CES) for symptoms of anxiety

Abstract: Background: Alpha-Stim AID is a self-administered, cranial electrotherapy stimulation (CES) device with evidence of effectiveness in treating symptoms of anxiety. In this study, Alpha-Stim AID was offered through a United Kingdom (UK) primary care social prescription service to patients with symptoms of anxiety. This study explored the experience and impact of using Alpha-Stim AID cranial electrotherapy stimulation (CES) through in-depth interviews. Methods: Out of a sample of 57 using Alpha-Stim AID, fifteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…The participants described reductions in their anxiety, improvements in mood and cognitive functioning, and increases in feelings of calmness and relaxation-some expressing it was akin to feelings experienced when meditating. This supports evidence from qualitative Alpha-Stim AID research (Griffiths et al, 2023) and quantitative research, which found Alpha-Stim AID significantly reduces anxiety symptoms (Barclay & Barclay, 2014;Griffiths et al, 2021;Griffiths et al, 2023;Morriss et al, 2019;Royal et al, 2022;Shekelle et al, 2018). Participants in this study linked benefits gained to the process of using Alpha-Stim AID, that this created a specified time for relaxation each day, which aligns with conclusions of other Alpha-Stim AID research (Morriss et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The participants described reductions in their anxiety, improvements in mood and cognitive functioning, and increases in feelings of calmness and relaxation-some expressing it was akin to feelings experienced when meditating. This supports evidence from qualitative Alpha-Stim AID research (Griffiths et al, 2023) and quantitative research, which found Alpha-Stim AID significantly reduces anxiety symptoms (Barclay & Barclay, 2014;Griffiths et al, 2021;Griffiths et al, 2023;Morriss et al, 2019;Royal et al, 2022;Shekelle et al, 2018). Participants in this study linked benefits gained to the process of using Alpha-Stim AID, that this created a specified time for relaxation each day, which aligns with conclusions of other Alpha-Stim AID research (Morriss et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
“…Participants found engagement with the Alpha-Stim AID was enabled through the useability of the device, in that it was accessible, easy to use, generally reliable, could be embedded into their daily routine, and did not have any adverse side effects preventing use; these factors promoted treatment compliance. The findings add to and align with evidence of useability, feasibility, ease of use, and lack of side effects found in other studies (Barclay & Barclay, 2014;Griffiths et al, 2021;Griffiths et al, 2023;Morriss et al, 2019;Royal et al, 2022;Shekelle et al, 2018). Medication side-effects can cause treatment failure (Sundbom & Bingefors, 2013); and the lack of Alpha-Stim AID side effects meant that some participants perceived the Alpha-Stim AID as a welcomed and preferred alternative to medication.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations